Arbuscular mycorrhizal fungi diversity in coffee (Coffea arabica) plantations on the Tacaná volcano, Chiapas, Mexico - Bertolini, Vincenzo; Montaño, Noé Manuel; Salazar-Ortuño, Blanca Larissa; Chimal-Sánchez, Eduardo; Varela, Lucía (Instituto de Ecología, A.C., 2020)
Background and Aims: Coffee is generating important incomes in the world, and particularly in Chiapas, Mexico. However, its production could be increased using arbuscular mycorrhizal fungi (AMF), without the need to substitute one type of coffee for another, as occurs in Mexico. This study estimated the diversity of AMF morphospecies in Coffea arabica plantations and examined its relationship with soil properties on the Tacaná volcano in the Soconusco region, Chiapas. Methods: Rhizospheric soil samples were collected in five plantations (Peloponeso, Montecristo, Chiquihuites, Finca Perú-París, and Barrio Nuevo) of C. arabica. AMF spores were extracted by wet sieving and decantation, and were mounted on slides with polyvinyl alcohol in lactoglycerol, with or without Melzer’s reagent. AMF morphospecies were identified by morphology of the spores, and their abundance, richness, and diversity were estimated and associated to some soil properties. Key results: A total of 10 genera and 27 morphospecies of AMF were recorded, and the abundance of AMF varied from 55 to 198 spores per 100 g of dry soil. Ambispora reticulata was a new record for Chiapas and Mexico. Acaulospora had the highest frequency and species richness. Chiquihuites had especially higher richness and diversity of AMF morphospecies with high abundances presumably associated to low levels of organic matter and PO4-3 in the soil. In the other plantations, richness and diversity of AMF morphospecies depended on soil acidity as driver of PO4-3 availability. Coffea arabica and C. canephora had similar richness, but different composition of AMF, comparing these results with a study on C. canephora. Conclusions: Coffea arabica favors the AMF richness compared to C. canephora. The PO4-3 availability and soil acidity together could regulate AMF diversity in C. arabica, favoring specific AMF in theses edaphic conditions. Acaulospora species and those genera only registered in C. arabica could be used as biofertilizers for its cultivation in Soconusco, Chiapas, Mexico.